Psychological Anthropology for the 21st Century - Eller, Jack David, author.
1 online resource (266 pages)
Keywords: This book provides a comprehensive introduction to psychological anthropology, covering both the early history and contemporary state of the field. Eller discusses the major themes, theories, figures and publications, and provides a detailed survey of the essential and enduring relationship between anthropology and psychology. The volume charts the development, celebrates the accomplishments, critiques the inadequacies, and considers the future of a field that has made great contributions to the overall discipline of anthropology. The chapters feature rich ethnographic examples and boxes for more in-depth discussion as well as summaries and questions to support teaching and learning. This is essential reading for all students new to the study of psychological anthropology.